Pengaruh Penjualan dan Biaya Operasional terhadap Laba Bersih pada PT Indocement Tunggal Prakarsa (Persero) Tbk Periode Tahun 2010-2017 - Endang Susilawati; Asep Mulyana (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2018)
This study aims to determine the influence of sales and operational costs on the net income both partially and simultaneously of PT Indocement Tunggal Prakarsa, Tbk. from 2010 to 2017. The type of research is descriptive verification by quantitative methods. Based on the results of the research showed that the sales and operational costs influence the net income simultaneously. Partially, sales and operational costs influenced on the net income.